Design of a Pitot Tube Cover with Smart Motion Detection Using Arduino and a Waterproof Ultrasonic Sensor for the Piper Seneca Aircraft - Untung L.N. Wibowo; Rizky Oscera E.; Dimas Endrawan Putra; Wisnu Kuncoro (PT Inovasi Pratama Internasional, 2025)
The research addressed the persistent issue of flight safety risk posed by failure to remove pitot tube covers during pre-flight checks on small aircraft, specifically the Piper Seneca V. An innovative solution was devised using a smart pitot tube cover integrated with a motion detection system based on waterproof ultrasonic sensors and an Arduino Uno microcontroller. The cover was designed to trigger a buzzer alarm automatically when movement was detected near the pitot tube and the cover remained installed. The development process involved both qualitative and quantitative approaches by incident interviews with pilots and instructors, design and assembly of hardware components, and field-experimentation on operational aircraft. The system underwent rigorous laboratory and real-world testing over a period of six months, covering various weather conditions and operational scenarios. Results demonstrated that the system reliably detected human presence within a 1–3 meter range, maintained a low error rate (average 4.2%), and produced an alarm response in under 310 milliseconds. In all test cases, the active system led to prompt inspection and removal of the pitot tube cover, thereby significantly reducing the risk of oversight. The final product exhibited robust performance, energy efficiency, and environmental resilience due to the use of waterproof materials and optimised component integration. It was concluded that the smart cover system enhances operational safety and awareness, offering a pragmatic preventive tool for the aviation training sector.